2022
DOI: 10.1021/acs.cgd.2c00678
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Excipients and Seeding on the Solid-State Form Transformation of Indomethacin during Liquid Antisolvent Precipitation

Abstract: Long-acting injectables are a unique drug formulation strategy, providing a slow and sustained release of active pharmaceutical ingredients (APIs). In this study, a novel approach that combines liquid antisolvent precipitation with seeding to obtain a stable form of the API indomethacin while achieving the desired particle size distribution is described. It was proven that when a metastable form of indomethacin was initially nucleated, the rate of its transformation to the stable form was influenced by the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 69 publications
(85 reference statements)
0
6
0
Order By: Relevance
“…In previous studies, [22][23][24][25][26][27][28] indomethacin (INM) (see Scheme 1 for its chemical structure) was used as a poorly water-soluble API model to analyze its thermodynamic and dissolution properties. With regard to INM, its most stable g-form (Form I, T m = 433 K) and a metastable a-form (Form II, T m = 426 K) are frequently studied in terms of the mechanisms of polymorph formation for the selective recovery of specic polymorphs, [32][33][34][35][36][37] and several other polymorphs and solvates are reported. 38,39 Kneading of INM with equimolar lidocaine (LDC, T m = 341 K) easily provides a eutectic mixture with an observed T m of 314 K. 25 We conrmed that LDC-analogous local anesthetics, procaine (PRC, T m = 334 K), tetracaine (TTC, T m = 316 K), and dibucaine (DBC, T m = 338 K) can also form eutectic mixtures, with melting points at 313, 303, and 325 K, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, [22][23][24][25][26][27][28] indomethacin (INM) (see Scheme 1 for its chemical structure) was used as a poorly water-soluble API model to analyze its thermodynamic and dissolution properties. With regard to INM, its most stable g-form (Form I, T m = 433 K) and a metastable a-form (Form II, T m = 426 K) are frequently studied in terms of the mechanisms of polymorph formation for the selective recovery of specic polymorphs, [32][33][34][35][36][37] and several other polymorphs and solvates are reported. 38,39 Kneading of INM with equimolar lidocaine (LDC, T m = 341 K) easily provides a eutectic mixture with an observed T m of 314 K. 25 We conrmed that LDC-analogous local anesthetics, procaine (PRC, T m = 334 K), tetracaine (TTC, T m = 316 K), and dibucaine (DBC, T m = 338 K) can also form eutectic mixtures, with melting points at 313, 303, and 325 K, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…1(b)). In antisolvent crystallization, the antisolvent or precipitant provides the driving force of the supersaturation of the solute (drug) by decreasing its solubility [28–34]. Antisolvent crystallization has numerous advantages compared to the other crystallization methods, such as low cost, ease of scale‐up, and superior control on the polymorph and size distribution of drug crystals, which can consequently lead to the enhancement of the final API solubility.…”
Section: Introductionmentioning
confidence: 99%
“…Hugo Silva et al pointed out that the LASC process can indeed be used as an alternative energy-efficient bottom-up method for the production of aqueous suspension-based LAIs with a reduced risk of contamination from milling equipment and fewer processing steps and that it may prove to be comparable in terms of stability and particle size distribution (PSD) to current industrially accepted top-down approaches [ 21 , 22 , 23 ]. Others, too, have demonstrated that this approach allows finetuning and control of drug product characteristics, such as PSD, crystallinity, and morphology, and that it is a simple, more sustainable, and less expensive process [ 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%